Diagnosis of Vitreoretinal Aspergillosis with Transvitreal Retinochoroidal Biopsy - Krishi Peddada; Nida M. Khan; Jascha Rubin; Haykanush Zakaryan; Yaobin Liu; Nikolay Popnikolov; Roshun Sangani; Weiye Li (Case Reports in Ophthalmological Medicine)
Diagnosing culture-proven endophthalmitis is complicated by the insufficient yield of intraocular samples and the variety of etiologies which mimic true endophthalmitis. In cases of impending vision loss where vitreous biopsy cannot provide a definitive diagnosis, transvitreal retinochoroidal biopsy can be an effective next step. Our case is a 48-year-old male with B-cell acute lymphoblastic leukemia that presented with counting fingers vision, redness, and tearing of the left eye. Exam showed cell and flare with hypopyon as well as dense vitritis. The patient underwent diagnostic pars plana vitrectomy and vitreous culture was negative at the time. Flow cytometry demonstrated no malignant cells. However, the patient’s vision and mental status continued to clinically decline despite being started on intravitreal and systemic antibiotic and antifungal therapy. Neuroimaging revealed rim-enhancing brain lesions. Transvitreal retinochoroidal biopsy was performed in an elevated area of the retina. The biopsy helped rule out malignancy and showed acute-angle, septate, branching hyphae characteristic of Aspergillus fumigatus. Ultimately, the vitreous biopsy, cultures, and a biopsy from the left frontal lobe brain abscess all confirmed this diagnosis as well. Transvitreal retinochoroidal biopsy can play a role in the diagnosis of a case of posterior uveitis and can be particularly effective in diagnosing a fungal endophthalmitis.